2011
DOI: 10.1093/cid/ciq206
|View full text |Cite
|
Sign up to set email alerts
|

 -D-Glucan Assay for the Diagnosis of Invasive Fungal Infections: A Meta-analysis

Abstract: We aimed to assess the accuracy of measuring serum or plasma (1→3)-β-D-glucan (BDG) for the diagnosis of invasive fungal infections (IFIs) by means of a meta-analysis of relevant studies. We searched in bibliographic databases for relevant cohort or case-control studies. We primarily compared BDG between patients with proven or probable IFIs (excluding Pneumocystis jirovecii infections), according to the criteria of the European Organization for Research and Treatment of Cancer/Mycoses Study Group or similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
288
5
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(312 citation statements)
references
References 48 publications
12
288
5
7
Order By: Relevance
“…Although the test is not Candida specific, it has been found to be a promising tool to diagnose invasive fungal infections, most of them being IC [6]. The accuracy of BDG for the diagnosis of invasive fungal infections has been discussed in a recent meta-analysis [7]. Also, a test based on the detection of antibodies against the surface of C. albicans germ tubes (CAGTA) has been commercialized [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the test is not Candida specific, it has been found to be a promising tool to diagnose invasive fungal infections, most of them being IC [6]. The accuracy of BDG for the diagnosis of invasive fungal infections has been discussed in a recent meta-analysis [7]. Also, a test based on the detection of antibodies against the surface of C. albicans germ tubes (CAGTA) has been commercialized [8].…”
Section: Introductionmentioning
confidence: 99%
“…61,62 With respect to serum BDG and GM assays, several meta-analyses have noted heterogeneity of results attributed to differences in study design, patient populations (e.g., hematologic vs other), the criteria used to define a positive test, and the definition of IA. [63][64][65][66][67][68] Among highrisk patients with hematologic malignancies and chemotherapy-induced neutropenia or allogeneic HCT, both tests share a similar sensitivity of 60%-80% and specificity of 90% and higher. 69 There may also be a role for combining serum BDG and GM screening in high-risk neutropenic patients.…”
Section: Improving Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%
“…Positive BDG test results were obtained before the results of any other conventional diagnostic method, including cultures, histopathology or radiological criteria, which may make it useful for early evaluation and preemptive initiation of appropriate antifungal treatment. A recent meta-analysis of 16 studies concluded that serum BDG measurement has a good diagnostic accuracy for IFD diagnosed in accordance with the EORTC/MSG criteria, with a pooled sensitivity of 76.8% and a specificity of 85.3% [97]. However, as with the GM studies, there was marked statistical heterogeneity among the studies [25].…”
Section: Antibody-targeted Biomarkersmentioning
confidence: 99%